2005
DOI: 10.1002/ijc.21187
|View full text |Cite
|
Sign up to set email alerts
|

Association of the BCRP C421A polymorphism with nonpapillary renal cell carcinoma

Abstract: Breast cancer resistance protein (BCRP), the second member of the ATP-binding cassette membrane transporter family, has a single nucleotide polymorphism, C421A (resulting in Q141K), that is of functional importance. Our aim was to explore the relationship between this polymorphism of the BCRP gene and the risk of renal cell carcinoma (RCC) development. For a case-control study, DNA samples from 200 nonpapillary RCC patients and 200 healthy control subjects were analyzed using the TaqMan technique. The genotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 37 publications
2
28
2
Order By: Relevance
“…An increased risk of DLBCL was associated with the 421A allele (P=0.042) and a worse survival was associated with the 34AA genotypes (hazard ratio, 3.69) in 156 DLBCL patients and 376 control subjects. In another study, a Japanese group found that the BCRP 421CC homozygotes were at a higher risk to develop non-papillary renal cell carcinoma (30). In the present study, BCRP 421C>A was significantly associated with the colorectal cancer risk (OR=16.12, 95% CI: 2.08-125.1), whereas distribution of the BCRP 34G>A genotypes did not significantly differ in the case and control groups (P=0.204).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…An increased risk of DLBCL was associated with the 421A allele (P=0.042) and a worse survival was associated with the 34AA genotypes (hazard ratio, 3.69) in 156 DLBCL patients and 376 control subjects. In another study, a Japanese group found that the BCRP 421CC homozygotes were at a higher risk to develop non-papillary renal cell carcinoma (30). In the present study, BCRP 421C>A was significantly associated with the colorectal cancer risk (OR=16.12, 95% CI: 2.08-125.1), whereas distribution of the BCRP 34G>A genotypes did not significantly differ in the case and control groups (P=0.204).…”
Section: Discussioncontrasting
confidence: 57%
“…The differential xenobiotic metabolism, which is due to variations in the transporter molecules, may affect the risk of certain types of cancers (26)(27)(28)(29)(30)(31). In certain studies, a possible role of transporter deficiencies was indicated in the susceptibility for colon carcinoma (14,18,32).…”
Section: Discussionmentioning
confidence: 99%
“…In RCC, an increase in ABCB1 expression (33,34) and activity (35) has been reported, suggesting a contribution of ABCB1 to the resistance of RCC to some anticancer drugs. Although polymorphisms in ABCB1 and ABCG2 may be associated with the development of RCC (36,37), it is currently not known whether polymorphisms in ABCB1 and ABCG2 are associated with the expression and function of these transporters at the somatic level in renal cancer cells (38). Nevertheless, the role of efflux transporters in tumor cells may be limited for acquired resistance to sunitinib, which may develop after an initial response to sunitinib, as acquired resistance to sunitinib may be more related to physiological changes in the microenvironment of tumors, allowing reestablishment of angiogenesis during sunitinib treatment (16).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the BCRP Q141K variant has been implicated in the altered pharmacokinetics of diflomotecan (Sparreboom et al, 2004). This BCRP polymorphism has also been associated with the susceptibility of renal carcinoma cells to drug treatments (Korenaga et al, 2005) and with the low expression of …”
Section: Discussionmentioning
confidence: 99%